Analysis of Success Factors of the Electronic Building Permit Service System through the Public Values Approach - Fitria Hedyanti; Reza Fathurrahman (Universitas Medan Area, 2022)
In terms of providing licensing services in the public sector, e-government provides a new nuance. The presence of the Online Building Permit (IMB) service, provided by the DKI Jakarta Provincial Investment and One-Stop Integrated Service (DPMPTSP), is sought to be a medium to cut possible financial and time costs associated with the licensing processes, to improve service quality, and also to eliminate the practice of brokers/licensing intermediaries. In practice, the level of intention to use this online IMB service among residents is relatively minimal. Based on this phenomenon, this research aims at analyzing the factors driving the success of e-Government through the public value approach. This study employs a qualitative descriptive method using the Theory of E-Government Success Model from De Lone and Mc Lean (2016) and Public Value proposed by Scott et al (2016). The research result reveals that DKI Jakarta DPMPTSP as a public organization has supported the provision of the online IMB service well, however, several factors need to be improved to increase the public value of the online IMB services to the community. Analysis of the five theoretical success measures (Trust, Well-Informedness, Communication, Information Retrieval, and Participation) is expected to explain the majority of citizens' perceptions of the success of e-Government.Â